Genomic analysis of prophages in 44 clinical strains of Pseudomonas aeruginosa isolated in Saudi Arabia - Alsaadi, Ahlam; Imam, Mohammed; Alghamdi, Abdulrahman A.; Aljedani, Safia S.; Alsari, Amal; Aljami, Haya; Bosaeed, Mohammad (Frontiers in Cellular and Infection Microbiology, 2025)
Prophages are bacteriophages that integrate their genomes into the bacterial chromosome. This research aimed to analyze and characterize prophages integrated into 44 Pseudomonas aeruginosa strains isolated from tertiary hospitals in Saudi Arabia. A total of 97 intact prophages were identified among clinical strains, with 16 prophages found present in more than one strain simultaneously. All prophages were found to have lengths ranging from 7.7 kb to 74.1 kb, and their GC content was found to be between 49.91% and 64.9%. Our findings show that prophages are present in the majority of the isolated P. aeruginosa strains (41 out of 44). Additionally, several proteins related to viral defense (toxin/antitoxin modules and proteins against restriction-modification enzymes) were identified, supporting the idea that prophages influence bacterial pathogenesis and anti-phage defenses.